Critical Factors Affecting Revisit Intention for the “Feel Restaurant” in Yangon, Myanmar - Zaw, Zin May; Nuangjamnong, Chompu (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2023)
Purpose: This research aims to investigate the impact of food quality, service quality, physical environment quality, and price on customer satisfaction and revisit intention at "Feel Restaurant" in Yangon, Myanmar. Research Design, Data, and Methodology: Utilizing primary and archival research approaches, this study examines factors influencing customer satisfaction and revisit intention. Data were collected from 384 respondents enjoying dining at Burmese Restaurants in Yangon. The researcher developed a new conceptual framework and incorporated two frameworks from previous studies to comprehensively determine the key factors influencing customer satisfaction and revisit intention. Results: The research findings reveal that price, physical environment quality, service quality, and food quality significantly affect customer satisfaction. Furthermore, customer satisfaction significantly influences revisit intention. Conclusions: The critical factors impacting the revisit intention of "Feel Restaurant" encompass price, physical environment quality, service quality, and food quality, contributing to customer satisfaction. Moreover, customer satisfaction was identified as affecting revisit intention in this Yangon, Myanmar restaurant. Limitations: Several limitations exist in identifying key factors influencing revisit intention. The study is geographically confined to Yangon, limiting its generalizability to other regions in Myanmar. This research specifically investigates key factors affecting revisit intention at "Feel Restaurant" in Yangon, Myanmar.